The Concept of Moral Education The Perspective of Al-Ghazali and Thomas Lickona - Anwar Sholeh; Devy Habibi Muhammad; Ari Susandi (STAIFAS-Press, 2022)
Morals are a determinant of whether or not a person is good, so that humans are able to adapt to their environment. The moral problem of this era makes moral education as the primary need of education. The study aims to: know the educational concepts of Akhlaq Al Ghozali ,Thomas Lickona and the similarities of difference. This research uses literature. data collection by method of assessment and analysis of data with comparatively transcribed. The results of research that discusses the concept of moral education sourced from Al-Imam Al-Ghazali and Thomas can be concluded including: 1) Moral education Al-Imam Al-Ghazali guided by the Qur'an and Sunnah by using four methods (exemplaryness, habituation, advice and stories) which the focus of the concept of moral education is the sacredness of the soul from all impurities and diseases of the heart so as to become a perfect human being (human being), 2) While Thomas's moral education is based on the family, environment and society as a source of moral education with five methods (understanding, discipleship, habituation, example and punishment) so that intelligent, intelligent and skilled human beings are realized, 3) Both Al Ghazali and Thomas broadly have the same concept of moral education, namely social dimensions, habits and examples.